Improving Critical Thinking Skills With The Help of STEAM (Science, Technology, Engineering, Art and Mathematics) on Business And Energy Material Description Questions. - Rasmi, Dian Periwi; Hendri, Menza; Yunicha, Tiara (Jurnal Pijar Mipa, 2025)
This research is a type of research and development using the Borg & Gall development model which consists of initial research and data collection stages, planning, product draft development, initial field trials, initial field trial revisions, main product tests and finally product refinement. At this stage, an assessment instrument with STEAM will be produced which is then validated by a team of experts which is then tested on students to determine the level of validity, reliability, level of difficulty and differentiation of questions. The subjects of the trial in this study are students of class X-E3 of SMA N 1 Jambi City which totals 20 students & students of class X-E1 SMA Adhyaksa 1 Jambi City which totals 20 students. The products produced in this development research are based on the results of the development and trials that have been carried out, it can be concluded that this STEAM loaded assessment instrument has been declared suitable for use from the results of the validation of the expert team and the analysis of question items.